A note on the optic characteristics of daylighting system via PMMA fibers. (15th October 2016) - Song, Jifeng; Zhu, Yong; Tong, Kai; Yang, Yongping; Reyes-Belmonte, M.A.
Highlights: Optic characteristics of daylighting system are studied by experiments. SDM reduces infrared thermal effects effectively protecting PMMA plastic fiber. Effect of incident angle on attenuation rate of fiber is revealed. Abstract: Polymethylmethacrylate (PMMA) plastic fiber has been used in daylighting system for a long time, however, the quantitative study of its optical properties is still limited. It has been verified in this paper that shortpass dichroic mirror (SDM) can effectively filter out up to 64% of infrared ray from high flux, resulting in small losses of visible spectrum of natural light. Experiments confirmed as well that SDM can significantly reduce infrared thermal effects effectively protecting PMMA plastic fiber. In addition, the effect of incidence angle on the attenuation of fiber is also measured. It has been proven that attenuation rate increases with the incident angle. Experimental data presented here can be used for daylighting system optimization using PMMA fibers.